Preparation method and application of double-atom catalyst for ammonia electrooxidation synchronous hydrogen production reaction

By regulating the active site spacing of the diatomic catalyst, high selectivity of ammonia nitrogen is converted into N2 and simultaneous hydrogen production is achieved, which solves the problem of low hydrogen production efficiency in the existing electrocatalytic ammonia oxidation technology and achieves high nitrogen selectivity and high effect on hydrogen production efficiency.

CN119352077APending Publication Date: 2025-01-24EAST CHINA JIAOTONG UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411055249.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the existing electrocatalytic ammonia oxidation technology, nano-scale catalysts have low hydrogen production efficiency during the ammonia oxidation reaction, which limits its application prospects.

Method used

The preparation method of a diatomic catalyst for the simultaneous hydrogen production reaction of ammonia electrooxidation is adopted. By regulating the spacing between the diatomic active sites, ammonia nitrogen is converted into N2 with high selectivity and hydrogen is simultaneously produced. The method includes pre-synthesizing a metal-organic framework with metal salt M1 and organic ligands, then reacting with metal salt M2 and thioacetamide to form a precursor, and pyrolyzing it in an inert atmosphere to obtain a diatomic catalyst.

Benefits of technology

It achieves high nitrogen selectivity and high hydrogen production efficiency in the electrocatalytic ammonia oxidation reaction. The NH4+-N conversion rate is 100%, and 99.7% is converted into N2. At the same time, the rate of hydrogen production at the cathode is high, and it has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352077A_ABST
    Figure CN119352077A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a diatomic catalyst for ammonia electrooxidation synchronous hydrogen production reaction, and the preparation method of the catalyst comprises the following steps: dissolving a metal salt M1 and an organic ligand in an organic solvent, stirring for reaction, washing the obtained material, and removing corresponding impurities to obtain a pre-synthesized metal organic framework; dissolving the metal salt M2 and thioacetamide in an organic solvent, stirring, adding the metal organic framework, continuously stirring, drying and grinding to obtain a precursor; the obtained precursor is heated and pyrolyzed in an inert atmosphere to obtain a diatomic catalyst, and the diatomic catalyst is loaded on a conductive substrate to prepare an electro-catalytic ammoxidation electrode which is applied to an ammonia electro-oxidation synchronous hydrogen production reaction. The electrode prepared from the diatomic catalyst on the basis of low cost has excellent ammonia oxidation activity, high ammonia nitrogen conversion rate and high nitrogen selectivity, and ammonia nitrogen is removed while hydrogen is produced. In addition, the catalyst is easy to prepare, low in cost, good in effect and easy to produce on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of diatomic catalysts, and in particular to a preparation method and application of diatomic catalysts for ammonia electrooxidation and simultaneous hydrogen production reactions. Background Art

[0002] Excessive ammonia nitrogen leads to eutrophication of water bodies and damages the ecosystem. However, ammonia is also considered to be a high hydrogen storage medium, easy to transport, low storage and transportation costs, and zero carbon emissions in terminal use, and is called "Hydrogen 2.0". Direct electrocatalytic ammonia oxidation technology is simple to operate, green and energy-saving. It can not only remove ammonia nitrogen pollution in wastewater, but also produce hydrogen energy, and has attracted much attention from researchers. Direct electrocatalytic ammonia oxidation technology relies on the ammonia oxidation reaction (AOR). However, due to the slow kinetics of AOR and the low efficiency of hydrogen production, its good application prospects are limited.

[0003] At present, the direct electrocatalytic ammonia oxidation mechanism is mainly based on the OS mechanism and GM mechanism of Pt-based catalysts. OS mechanism: NH3 molecules gradually dehydrogenate to form *N, NN combines to form N2, or *N continues to oxidize to form NO3 - 、NO2 - The GM mechanism proposes that NH3 molecules are gradually dehydrogenated to form *NH2, *NH, and the reaction intermediate *NH x Can polymerize to produce hydrazine intermediate *N2H x , followed by further oxidative dehydrogenation, and finally producing N2 (* indicates active sites). Direct electrocatalytic ammonia oxidation catalysts are mainly nanoscale metal catalysts, composed of nanoparticles and subnanoclusters of different particle sizes, with various active sites of different crystal faces, vertices and interfaces, expressing catalytic activity in an assembled and diversified manner, and the complex reaction process leads to product diversity. However, as the catalyst develops from the nanoscale to the atomic level, it exhibits excellent catalytic performance and high product selectivity. And by utilizing the synergistic effect of adjacent positions between metal atoms, metal diatomic catalysts can improve the catalytic performance to a greater extent. Positioning the two metal atom active sites in adjacent positions enables the reactants to be directly polymerized at the dual sites to produce the target product, so that the electrocatalytic ammonia oxidation follows the GM mechanism to generate hydrazine and then highly selectively generates N2, improving the catalytic performance while avoiding the generation of product diversity in multi-step reactions. For example, a dual-metal site single-atom catalyst proposed in Chinese patent document CN202211440397.7 has extremely high electrocatalytic ammonia oxidation performance and product selectivity, and can achieve full denitrification effect. Therefore, the existing catalysts can exhibit excellent catalytic performance and high product selectivity, but have not improved the hydrogen production efficiency in direct electrocatalytic ammonia oxidation technology. Summary of the invention

[0004] The present invention aims at the problem of low hydrogen production efficiency in the existing nano-scale catalysts in the field of electrocatalytic ammonia oxidation technology in the AOR process in order to achieve the purpose of complete denitrification, and proposes a preparation method and application of a diatomic catalyst for ammonia electrooxidation and simultaneous hydrogen production reaction. By regulating the distance between the diatomic active sites, the green and highly selective conversion of ammonia nitrogen into N2 is achieved, and simultaneous hydrogen production is achieved.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: In one aspect, the present invention provides a method for preparing a diatomic catalyst for ammonia electrooxidation and simultaneous hydrogen production reaction, comprising the following steps: (1) dissolving the metal salt M1 and the organic ligand in an organic solvent, stirring and washing the obtained material to remove impurities, thereby obtaining a pre-synthesized metal organic framework; (2) first dissolving the metal salt M2 and thioacetamide in an organic solvent, adding the metal organic framework after stirring, continuing to stir for a period of time, and then drying and grinding to obtain a precursor; (3) The precursor obtained in step (2) is heated and pyrolyzed in an inert atmosphere, and then ground after cooling. The powdered solid obtained after grinding is acid-washed, and then washed and dried to obtain a diatomic catalyst.

[0006] The present invention first synthesizes the organic ligand and the metal salt M1 in advance to prepare a metal organic framework (MOF). Based on the Lewis acid-base theory, thioacetamide can effectively control the atomic distance between the metal atom M1 and the metal atom M2 to Forming an asymmetric coordination structure. After carbonization under an inert atmosphere, MOF can form a three-dimensional porous carbon structure with high porosity, which allows the diatomic catalyst to expose more active sites, expand the contact area between the solution and the catalyst, and enhance the AOR reaction activity.

[0007] The present invention successfully synthesized asymmetric coordination environment metal diatomic catalysts. The structural design of controlling the atomic distance is the key to achieving high hydrogen production in electrocatalytic ammonia oxidation. The diatomic material successfully controlled the diatomic distance within The electrocatalytic ammonia oxidation follows the GM mechanism to generate hydrazine and then generate nitrogen with high selectivity. The present invention successfully prepares a diatomic catalyst with high ammonia oxidation activity, high ammonia nitrogen conversion rate and high nitrogen selectivity on the basis of ensuring low-cost preparation. The present invention provides a favorable guarantee for the development of electrocatalytic ammonia oxidation catalysts with high nitrogen selectivity and low cost based on atomic structure design.

[0008] Preferably, in the obtained diatomic catalyst, the distance between the diatomic active sites is

[0009] Preferably, the metal salt M1 is selected from one or more of zinc chloride, zinc sulfate, zinc nitrate, zinc gluconate, zinc acetate and their solutions.

[0010] Preferably, the metal salt M2 is selected from one or more of chlorides, sulfates, nitrates and acetates of nickel, cobalt, chromium, copper, iron and manganese.

[0011] Preferably, the molar ratio of zinc salt to metal salt is 1-1.5:0.5-1.

[0012] Preferably, the mass ratio of the metal salt M1 to the organic ligand added in step (1) is 15-25:10-15.

[0013] Preferably, the molar ratio of the metal salt M2 and thioacetamide added in step (2) is 3-4:8-12.

[0014] Preferably, the organic ligand in step (1) is dimethylimidazole.

[0015] Preferably, the organic solvent in step (1) and step (2) can be selected from one of methanol, ethanol and butanol, and the stirring time is 12 to 24 hours.

[0016] Preferably, the heating temperature in step (3) is 800-1000° C., and the pyrolysis time is 1-3 h.

[0017] On the other hand, the present invention proposes an application of a diatomic catalyst for ammonia electrooxidation and simultaneous hydrogen production reaction, wherein the diatomic catalyst is loaded on a conductive substrate to prepare a diatomic ammonia electrocatalytic oxidation electrode, and the diatomic ammonia electrocatalytic oxidation electrode is used in ammonia electrooxidation and simultaneous hydrogen production reaction.

[0018] Preferably, the loading amount of the diatomic catalyst on the conductive substrate is 0.5 to 3 mg / cm 2 .

[0019] Therefore, the present invention has the following beneficial effects: (1) The spacing between the diatomic active sites in the present invention is successfully controlled based on the Lewis acid-base theory. The electrocatalytic ammonia oxidation follows the GM mechanism to generate hydrazine and then highly selectively generate nitrogen. Dimethylimidazole and zinc salt M1 form a metal organic framework (MOF), which can form a three-dimensional porous carbon structure with high porosity, so that the diatomic catalyst exposes more active sites and thus enhances the AOR reaction activity.

[0020] (2) The catalyst prepared by the present invention is simple to operate and environmentally friendly on the basis of effectively controlling costs. The prepared diatomic ammonia electrocatalytic oxidation electrode is used in practical applications to produce NH4 +-N conversion rate is 100%, while 99.7% is converted to N2 with high conversion rate. In the electrochemical reaction, the cathode can produce hydrogen at a rate of 0.34483mmol·mg while converting to N2 -1 ·h -1 , has good hydrogen production efficiency and has broad application prospects. It can have good hydrogen production efficiency while maintaining a high nitrogen conversion rate.

[0021] (3) This invention provides a new idea for developing high-quality, low-cost AOR catalysts based on atomic structure design. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 (a) HAADF-STEM image of the diatomic catalyst Ni-Zn@SNC prepared in Example 1; Figure 1 (b) Figure 1 (a) The locally enlarged HAADF-STEM image of the dotted line part; Figure 1 (c) Yes Figure 1 (b) Schematic diagram of the electron intensity image around the positions marked with #1, #2, and #3; Figure 1 (d) Yes Figure 1 Gaussian fits of the diatomic distances obtained for all circles in (b).

[0023] Figure 2 This is a cyclic voltammetry (CV) test data diagram of the Ni-Zn@SNC diatomic electrocatalytic ammonia oxidation electrode prepared in Example 1 of the present invention.

[0024] Figure 3 It is a comparison diagram of the electrochemical performance of the diatomic electrocatalytic ammonia oxidation electrodes prepared in Example 1 of the present invention and Comparative Examples 1 to 4; Figure 3 (a) is a comparison diagram of current density; Figure 3 (b) is a resistance comparison diagram; Figure 3 (c) is a comparison diagram of electrode potential; Figure 3 (d) is a comparison diagram of specific capacitance.

[0025] Figure 4 It is a comparison diagram of ammonia nitrogen conversion effect of the diatomic electrocatalytic ammonia oxidation electrode prepared in Example 1 of the present invention and Comparative Examples 1 to 4, and a comparison diagram of cathode hydrogen production; Figure 4 (a) is a comparison chart of ammonia nitrogen removal rate; Figure 4 (b) is a comparison chart of nitrite nitrogen removal rate; Figure 4 (c) is a comparison chart of ammonia nitrogen removal effects; Figure 4 (d) is a comparison chart of cathode hydrogen production rate.

[0026] Figure 5This is the test result of the Ni-Zn@SNC diatomic electrocatalytic ammonia oxidation electrode prepared in Example 1 of the present invention in simulated wastewater with different initial ammonia nitrogen concentrations; Figure 5 (a) is a comparison chart of ammonia nitrogen removal rate; Figure 5 (b) is a comparison chart of nitrite nitrogen removal rate; Figure 5 (c) is a comparison chart of ammonia nitrogen removal effects; Figure 5 (d) is a comparison chart of cathode hydrogen production rate.

[0027] Figure 6 This is a graph showing the gas generation amount and time of the Ni-Zn@SNC diatomic electrocatalytic ammonia oxidation electrode prepared in Example 1 of the present invention.

[0028] Figure 7 This is the test result of the cycling durability experiment of the diatomic catalyst Ni-Zn@SNC prepared in Example 1 of the present invention in photovoltaic wastewater; Figure 7 (a) is a graph showing changes in ammonium ion content; Figure 7 (b) is a comparison chart of ammonia nitrogen removal rates; Figure 7 (c) is a graph showing changes in nitrate nitrogen content; Figure 7 (d) is a comparison chart of energy consumption (EC) and Faraday efficiency (FE).

[0029] Figure 8 (a) is a schematic diagram of the Gibbs free energy of the AOR mechanism pathway on Ni-Zn@SNC and Ni@SNC; Figure 8 (b) is the PDOS (active sites) of different electrodes, and the dotted line represents the Fermi level; Figure 8 (c) is the d-band center of Zn and Ni atoms in different electrodes. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below through specific implementation cases, and specific implementation operation processes and methods are given, but the protection scope of the present invention is not limited to the following implementation cases.

[0031] Overall embodiment: A method for preparing a diatomic catalyst for ammonia electrooxidation and simultaneous hydrogen production reaction comprises the following steps: (1) Synthesis of metal organic framework: The metal salt M1 and the organic ligand are dissolved in an organic solvent (methanol), stirred, and centrifuged. The obtained material is washed with ultrapure water and methanol to remove impurities, thereby obtaining a pre-synthesized metal organic framework.

[0032] (2) Synthesis of diatomic catalyst precursor: First, dissolve the metal salt M2 and thioacetamide in an organic solvent, add the metal organic framework after ultrasonic mixing and continue stirring for a period of time, and then dry and grind to obtain the diatomic catalyst precursor powder.

[0033] (3) Synthesis of finished diatomic catalyst: The diatomic catalyst precursor powder obtained in step (2) is heated and pyrolyzed in an inert atmosphere, ground after cooling, and the powdered solid obtained after grinding is acid-washed, then washed with deionized water and methanol, dried and stored in N2 to obtain a diatomic catalyst.

[0034] In the present invention, preferably, the distance between the diatomic active sites of the metal atom M1 and the metal atom M2 obtained by pyrolysis of the metal salt M1 and the metal salt M2 is Preferably, the mass ratio of the metal salt M1 added in step (1) to the organic ligand is 15-25:10-15. The molar ratio of the metal salt M2 added in step (2) to thioacetamide is 3-4:8-12. Preferably, the metal salt M1 is selected from one or more of zinc chloride, zinc sulfate, zinc nitrate, zinc gluconate, zinc acetate and their water and products. The metal salt M2 is selected from one or more of chlorides, sulfates, nitrates and acetates of nickel, cobalt, chromium, copper, iron and manganese. Preferably, the heating temperature in step (3) is 800-1000°C and the pyrolysis time is 1-3h.

[0035] A diatomic catalytic ammonia oxidation electrode, the preparation method of which is: subjecting a diatomic catalyst, Nafion, ethylene glycol and ethanol to ultrasonic treatment for 15 minutes to form a uniform ink-like slurry, coating the slurry on the surface of carbon paper (CP), and drying the slurry in air to obtain an electrocatalytic ammonia oxidation electrode of the diatomic catalyst.

[0036] In the present invention, the loading amount of the diatomic catalyst on the conductive substrate is preferably 0.5 to 3 mg / cm 2 .

[0037] Example 1 A method for preparing a nickel-zinc diatomic catalyst comprises the following steps: (1) Synthesis of metal organic framework (ZIF-8): 3.3 g 2-methylimidazole (70 mL methanol) and 1.5 g Zn(NO3)2·6H2O (70 mL methanol) were mixed in a beaker and stirred for 24 h. The ZIF-8 obtained after centrifugation was removed from the corresponding impurities with ultrapure water and methanol and placed in a vacuum oven at 80 °C overnight.

[0038] (2) Synthesis of nickel-zinc diatomic catalyst (Ni-Zn@SNC catalyst) precursor: 200 mg ZIF-8 and 20 mL methanol were mixed in beaker A and ultrasonicated for about 30 minutes. 0.08 mmol Ni(NO3)2·6H2O, 2.4 mmol thioacetamide, and 10 mL methanol were placed in another beaker B and stirred for 1 hour. An appropriate amount of the solution in beaker B was added to beaker A and stirred for 1 hour. The material obtained after centrifugation was placed in a vacuum at natural temperature for 24 hours to obtain a dry powder of nickel-zinc diatomic catalyst (Ni-Zn@SNC catalyst) precursor.

[0039] (3) Preparation of finished nickel-zinc diatomic catalyst (Ni-Zn@SNC catalyst): The dry powder of the nickel-zinc diatomic catalyst (Ni-Zn@SNC catalyst) precursor was heated in N2 gas at 900°C for 3 hours and cooled to natural temperature. The carbon powder was leached with 0.5 mol / L H2SO4 at natural temperature for 12 hours, the corresponding impurities were removed with deionized water and methanol, and the black powder was placed in a vacuum drying oven at 60°C for 12 hours to obtain the black powder, which was ground and stored in N2 atmosphere. The black powder is the finished Ni-Zn@SNC catalyst.

[0040] A diatomic catalytic ammonia oxidation electrode is prepared by ultrasonicating Ni-Zn@SNC catalyst (10 mg), Nafion (50 μL), ethylene glycol (200 μL) and ethanol (800 μL) for 15 min to form a uniform ink-like slurry, which is then coated on the surface of carbon paper (CP) with a catalyst loading of about 2 mg / cm 2 , and dried in air to obtain the Ni-Zn@SNC electrocatalytic ammonia oxidation electrode.

[0041] High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of Ni-Zn@SNC ( Figure 1 (a) confirms that the large number of bright spots are single metal atoms, due to their higher reflected electron intensity than the surrounding non-metallic elements dispersed in the carbon matrix. HAADF-STEM image at a higher magnification ( Figure 1 (b)) further shows clear atomic pairs (yellow circles). The different reflected electron intensities of the metal atomic pairs indicate that the adjacent bright spots prove to be coupled heterogeneous Ni and Zn single atoms ( Figure 1 (c)). Figure 1 (d) indicates that The distance between the two atoms in Ni-Zn@SNC is the main distance between the two atoms. According to the Gaussian fitting results, the distance between these pairs of atoms is mostly

[0042] Example 2 A method for preparing a zinc-cobalt diatomic catalyst comprises the following steps: (1) Synthesis of metal organic framework (ZIF-8): 3.3 g 2-methylimidazole (70 mL methanol) and 1.5 g Zn(NO3)2·6H2O (70 mL methanol) were mixed in a beaker and stirred for 24 h. The ZIF-8 obtained after centrifugation was removed from the corresponding impurities with ultrapure water and methanol and placed in a vacuum oven at 80 °C overnight.

[0043] (2) Synthesis of zinc-cobalt diatomic catalyst (Zn-Co@SNC catalyst) precursor: 200 mg ZIF-8 and 20 mL methanol were mixed in beaker A and ultrasonicated for about 30 minutes. 0.08 mmol Co(NO3)2, 2.4 mmol thioacetamide, and 10 mL methanol were placed in another beaker B and stirred for 1 hour. An appropriate amount of the solution in beaker B was added to beaker A and stirred for 1 hour. The material obtained after centrifugation was placed in a vacuum at natural temperature for 24 hours to obtain a dry powder of zinc-cobalt diatomic catalyst (Zn-Co@SNC catalyst) precursor.

[0044] (3) Preparation of finished zinc-cobalt diatomic catalyst (Zn-Co@SNC catalyst): The dry powder of zinc-cobalt diatomic catalyst (Zn-Co@SNC catalyst) precursor was heated in N2 gas at 900°C for 3 hours and cooled to natural temperature. The carbon powder was leached with 0.5 mol / L H2SO4 at natural temperature for 12 hours, the corresponding impurities were removed with deionized water and methanol, and the black powder was placed in a vacuum drying oven at 60°C for 12 hours to obtain the black powder, which was ground and stored in N2 atmosphere. The black powder is the finished Zn-Co@SNC catalyst.

[0045] A diatomic catalytic ammonia oxidation electrode is prepared by ultrasonicating Zn-Co@SNC catalyst (10 mg), Nafion (50 μL), ethylene glycol (200 μL) and ethanol (800 μL) for 15 min to form a uniform ink-like slurry, which is then coated on the surface of carbon paper (CP) with a catalyst loading of about 2 mg / cm 2 , and dried in air to obtain the Zn-Co@SNC electrocatalytic ammonia oxidation electrode.

[0046] Example 3 A method for preparing a zinc-copper diatomic catalyst comprises the following steps: (1) Synthesis of metal organic framework (ZIF-8): 3.3 g 2-methylimidazole (70 mL methanol) and 1.5 g Zn(NO3)2·6H2O (70 mL methanol) were mixed in a beaker and stirred for 24 h. The ZIF-8 obtained after centrifugation was removed from the corresponding impurities with ultrapure water and methanol and dried in a vacuum oven at 80 °C overnight.

[0047] (2) Synthesis of zinc-copper diatomic catalyst (Zn-Cu@SNC catalyst) precursor: 200 mg ZIF-8 and 20 mL methanol were mixed in beaker A and ultrasonicated for about 30 minutes. 0.08 mmol Cu(NO3)2, 2.4 mmol thioacetamide, and 10 mL methanol were placed in another beaker B and stirred for 1 hour. An appropriate amount of the solution in beaker B was added to beaker A and stirred for 1 hour. The material obtained after centrifugation was placed in a vacuum at natural temperature for 24 hours to obtain a dry powder of zinc-copper diatomic catalyst (Zn-Cu@SNC catalyst) precursor.

[0048] (3) Preparation of finished zinc-copper diatomic catalyst (Zn-Cu@SNC catalyst): The precursor dry powder of zinc-copper diatomic catalyst (Zn-Cu@SNC catalyst) was heated in N2 gas at 900°C for 3 hours and cooled to natural temperature. The carbon powder was leached with 0.5 mol / L H2SO4 at natural temperature for 12 hours, and the corresponding impurities were removed with deionized water and methanol. The black powder was placed in a vacuum drying oven at 60°C for 12 hours to obtain a black powder. The black powder was ground and stored in N2 atmosphere. The black powder is the finished Zn-Cu@SNC catalyst.

[0049] A diatomic catalytic ammonia oxidation electrode is prepared by ultrasonicating Zn-Cu@SNC catalyst (10 mg), Nafion (50 μL), ethylene glycol (200 μL) and ethanol (800 μL) for 15 min to form a uniform ink-like slurry, which is then coated on the surface of carbon paper (CP) with a catalyst loading of about 2 mg / cm 2 , and dried in air to obtain the Zn-Cu@SNC electrocatalytic ammonia oxidation electrode.

[0050] Example 4 A method for preparing a zinc-manganese diatomic catalyst comprises the following steps: (1) Synthesis of metal organic framework (ZIF-8): 3.3 g 2-methylimidazole (70 mL methanol) and 1.5 g Zn(NO3)2·6H2O (70 mL methanol) were mixed in a beaker and stirred for 24 h. The ZIF-8 obtained after centrifugation was removed from the corresponding impurities with ultrapure water and methanol and dried in a vacuum oven at 80 °C overnight.

[0051] (2) Synthesis of zinc-manganese diatomic catalyst (Zn-Mn@SNC catalyst) precursor: 200 mg ZIF-8 and 20 mL methanol were mixed in beaker A and ultrasonicated for about 30 minutes. 0.08 mmol Mn(NO3)2, 2.4 mmol thioacetamide, and 10 mL methanol were placed in another beaker B and stirred for 1 hour. An appropriate amount of the solution in beaker B was added to beaker A and stirred for 1 hour. The material obtained after centrifugation was placed in a vacuum at natural temperature for 24 hours to obtain a dry powder of zinc-manganese diatomic catalyst (Zn-Mn@SNC catalyst) precursor.

[0052] (3) Preparation of finished zinc-manganese diatomic catalyst (Zn-Mn@SNC catalyst): The dry powder of zinc-manganese diatomic catalyst (Zn-Mn@SNC catalyst) precursor was heated in N2 gas at 900°C for 3 hours and cooled to natural temperature. The carbon powder was leached with 0.5 mol / L H2SO4 at natural temperature for 12 hours, the corresponding impurities were removed with deionized water and methanol, and the black powder was placed in a vacuum drying oven at 60°C for 12 hours to obtain the black powder, which was ground and stored in N2 atmosphere. The black powder is the finished Zn-Mn@SNC catalyst.

[0053] A diatomic electrocatalytic ammonia oxidation electrode is prepared by ultrasonicating a Zn-Mn@SNC catalyst (10 mg), Nafion (50 μL), ethylene glycol (200 μL) and ethanol (800 μL) for 15 min to form a uniform ink-like slurry, which is then coated on the surface of carbon paper (CP) with a catalyst loading of about 2 mg / cm 2 , and dried in air to obtain the Zn-Mn@SNC electrocatalytic ammonia oxidation electrode.

[0054] Comparative Example 1 (Ni-Zn@NC catalyst) (1) Synthesis of metal organic framework (ZIF-8): 3.3 g 2-methylimidazole (70 mL methanol) and 1.5 g Zn(NO3)2·6H2O (70 mL methanol) were mixed in a beaker and stirred for 24 h. The ZIF-8 obtained after centrifugation was removed from the corresponding impurities with ultrapure water and methanol and placed in a vacuum oven at 80 °C overnight.

[0055] (2) Synthesis of Ni-Zn@NC catalyst precursor: 200 mg ZIF-8 and 20 mL methanol were mixed in beaker A and ultrasonicated for about 30 minutes. 0.08 mmol Ni(NO3)2·6H2O and 2.4 mmol thioacetamide were placed in another beaker B and stirred for 1 hour. An appropriate amount of the solution in beaker B was added to beaker A and stirred for 1 hour. The material obtained after centrifugation was placed in a vacuum at natural temperature for 24 hours to obtain a dry powder of Ni-Zn@NC catalyst precursor.

[0056] (3) Preparation of Ni-Zn@NC catalyst product: The Ni-Zn@NC catalyst precursor dry powder was heated in N2 gas at 900°C for 3 hours and cooled to natural temperature. The carbon powder was leached with 0.5 mol / L H2SO4 at natural temperature for 12 hours, the corresponding impurities were removed with deionized water and methanol, and the black powder was placed in a vacuum drying oven at 60°C for 12 hours to obtain the black powder. The black powder was ground and stored in N2 atmosphere. The black powder is the Ni-Zn@NC catalyst product.

[0057] A diatomic electrocatalytic ammonia oxidation electrode is prepared by ultrasonicating Ni-Zn@NC catalyst (10 mg), Nafion (50 μL), ethylene glycol (200 μL) and ethanol (800 μL) for 15 min to form a uniform ink-like slurry, which is then coated on the surface of carbon paper (CP) with a catalyst loading of about 2 mg / cm 2 , and dried in air to obtain the Ni-Zn@NC electrocatalytic ammonia oxidation electrode.

[0058] Comparative Example 2 (Ni@SNC catalyst) (1) Synthesis of metal organic framework (ZIF-8): 3.3 g 2-methylimidazole (70 mL methanol) and 1.5 g Zn(NO3)2·6H2O (70 mL methanol) were mixed in a beaker and stirred for 24 h. The ZIF-8 obtained after centrifugation was removed from the corresponding impurities with ultrapure water and methanol and placed in a vacuum oven at 80 °C overnight.

[0059] (2) Synthesis of Ni@SNC catalyst precursor: 200 mg ZIF-8 and 20 mL methanol were mixed in beaker a and ultrasonicated for about 30 minutes. 0.08 mmol Ni(NO3)2·6H2O, 2.4 mmol thioacetamide, and 10 mL methanol were placed in another beaker B and stirred for 1 hour. Heating temperature was 950°C for 15 min. An appropriate amount of the solution in beaker B was added to beaker A and stirred for 1 hour. The material obtained after centrifugation was placed in a vacuum at natural temperature for 24 hours to obtain a dry powder of Ni@SNC catalyst precursor.

[0060] (3) Preparation of Ni@SNC catalyst product: The Ni@SNC catalyst precursor dry powder was heated in N2 gas at 900°C for 3 hours and cooled to natural temperature. The carbon powder was leached with 0.5 mol / L H2SO4 at natural temperature for 12 hours, the corresponding impurities were removed with deionized water and methanol, and the black powder was placed in a vacuum drying oven at 60°C for 12 hours to obtain the black powder. The black powder was ground and stored in N2 atmosphere. The black powder is the Ni@SNC catalyst product.

[0061] A diatomic electrocatalytic ammonia oxidation electrode is prepared by ultrasonicating Ni@SNC catalyst (10 mg), Nafion (50 μL), ethylene glycol (200 μL) and ethanol (800 μL) for 15 min to form a uniform ink-like slurry, which is then coated on the surface of carbon paper (CP) with a catalyst loading of about 2 mg / cm 2 , and dried in air to obtain the Ni@SNC electrocatalytic ammonia oxidation electrode.

[0062] Comparative Example 3 (Zn@SNC Catalyst) (1) Synthesis of metal organic framework (ZIF-8): 3.3 g 2-methylimidazole (70 mL methanol) and 1.5 g Zn(NO3)2·6H2O (70 mL methanol) were mixed in a beaker and stirred for 24 h. The ZIF-8 obtained after centrifugation was removed from the corresponding impurities with ultrapure water and methanol and placed in a vacuum oven at 80 °C overnight.

[0063] (2) Synthesis of Zn@SNC catalyst precursor: 200 mg ZIF-8 and 20 mL methanol were mixed in beaker A and ultrasonicated for about 30 minutes. 2.4 mmol thioacetamide and 10 mL methanol were placed in another beaker B and stirred for 1 hour. The material obtained after centrifugation was placed in vacuum at natural temperature for 24 hours to obtain Zn@SNC catalyst precursor dry powder.

[0064] (3) Preparation of Zn@SNC catalyst product: The Zn@SNC catalyst precursor dry powder was heated in N2 gas at 900°C for 3 hours and cooled to natural temperature. The carbon powder was leached with 0.5 mol / L H2SO4 at natural temperature for 12 hours, the corresponding impurities were removed with deionized water and methanol, and the black powder was placed in a vacuum drying oven at 60°C for 12 hours to obtain the black powder. The black powder was ground and stored in N2 atmosphere. The black powder is the Zn@SNC catalyst product.

[0065] A diatomic electrocatalytic ammonia oxidation electrode is prepared by ultrasonicating Zn@SNC catalyst (10 mg), Nafion (50 μL), ethylene glycol (200 μL) and ethanol (800 μL) for 15 min to form a uniform ink-like slurry, which is then coated on the surface of carbon paper (CP) with a catalyst loading of about 2 mg / cm 2 , and dried in air to obtain the Zn@SNC electrocatalytic ammonia oxidation electrode.

[0066] Comparative Example 4 (NCN Catalyst) Synthesis of NCN catalyst: 3.3 g 2-methylimidazole (70 mL methanol) and 1.5 g Zn(NO3)2·6H2O (70 mL methanol) were mixed in a beaker and stirred for 24 h. The resulting material was centrifuged and the corresponding impurities were removed using ultrapure water and methanol. The material was placed in a vacuum oven at 80 °C overnight to obtain the NCN catalyst.

[0067] A diatomic electrocatalytic ammonia oxidation electrode is prepared by ultrasonicating NCN catalyst (10 mg), Nafion (50 μL), ethylene glycol (200 μL) and ethanol (800 μL) for 15 min to form a uniform ink-like slurry, which is then coated on the surface of carbon paper (CP) with a catalyst loading of about 2 mg / cm 2 , and dried in air to obtain the NCN electrocatalytic ammonia oxidation electrode.

[0068] The Zn-Ni@SNC diatomic electrocatalytic ammonia oxidation electrode prepared in Example 1 was used to study the ammonia oxidation activity. The method was as follows: using the Zn-Ni@SNC electrode as the working electrode, Hg / HgO as the reference electrode, and Pt wire as the counter electrode to form a three-electrode system, the ammonia oxidation performance was studied by cyclic voltammetry in 1 mol / L KOH and 1 mol / L KOH + 0.05 mol / L (NH4)2SO4. Figure 2 The CV test results show that by comparing the CV curves in the presence and absence of ammonia solution, it is observed that the Ni-Zn@SNC diatomic electrocatalytic ammonia oxidation electrode has a significant improvement in the catalytic activity of the AOR reaction.

[0069] The electrochemical performance of the electrocatalytic ammonia oxidation electrode prepared in the above comparative example was investigated using the above three-electrode system. Figure 3 The test results show that compared with other catalytic electrodes, the Ni-Zn@SNC catalytic electrode has a maximum current density of 15.52 mA / cm 2 @0.7V; also has the smallest charge transfer resistance (R ct ), only 1.24Ω; Ni-Zn@SNC exhibits the smallest Tafel slope (73.14mVdec -1 ); the best electrochemically active specific surface area (66.0 cm 2 ), it can be proved from the above data that the Ni-Zn@SNC diatomic electrocatalytic ammonia oxidation electrode prepared in Example 1 has a more excellent AOR electrochemical performance than that of Comparative Examples 1 to 4.

[0070] The practical application performance of the electrocatalytic ammonia oxidation electrode prepared in the above comparative example was investigated. The above three-electrode system was used to carry out the experiment. The initial NH4 + -N concentration is 2500 mg L -1The test results are shown in Figure 2. Figure 4 As shown, the NH4 + The ammonia nitrogen conversion efficiency of the Ni-Zn@SNC catalyst prepared in Example 1 was as high as 100%, generating only 7.675 mg L -1 NO2 - -N, 99.7% converted to N2, and the conversion rate of N2 was also high. The electrocatalytic system constructed by Ni-Zn@SNC catalytic anode showed the best hydrogen production effect, with a hydrogen production rate of 0.34483mmol·mg -1 ·h -1 .

[0071] The actual application performance of the Zn-Ni@SNC diatomic electrocatalytic ammonia oxidation electrode prepared in Example 1 was investigated. The above three-electrode system was used to carry out a 20-hour actual denitrification experiment in simulated wastewater with ammonia nitrogen concentration of 1340, 2563, and 5589 mg / L, respectively. The test results are as follows: Figure 5 NH4 + The conversion efficiency of -N is 100%, 100% and 89.33% respectively, and the N2 selectivity exceeds 99% under different concentrations. The cathode hydrogen production rate also increases almost proportionally with the increase of concentration. Figure 6 The hydrogen production curve is shown in Figure 1. The Zn-Ni@SNC diatomic electrocatalytic ammonia oxidation electrode prepared in Example 1 can maintain a good hydrogen production rate while maintaining high N2 selectivity.

[0072] The denitrification performance and cycle durability of the Zn-Ni@SNC diatomic electrocatalytic ammonia oxidation electrode prepared in Example 1 were investigated in actual wastewater using the three-electrode system. The test results are shown in Figure 1. Figure 7 As shown in the figure, a 150-hour cycle experiment was carried out in photovoltaic wastewater, and the initial ammonia concentration was about 3300 mg / L. After 5 cycles, the NH4 + -N removal rate is still 54.97%, N2 selectivity is above 99.5%, and energy consumption (EC) is less than 0.23kWh / kgN. Experimental data show that the Zn-Ni@SNC diatomic electrocatalytic ammonia oxidation electrode prepared in Example 1 can maintain good catalytic activity and high N2 selectivity during long-term catalytic oxidation reaction, while also controlling low energy consumption, proving that the Zn-Ni@SNC diatomic catalyst prepared in Example 1 can be put into a wide range of applications with high quality and low cost.

[0073] The free energy diagrams of different structures of the diatomic electrocatalytic ammonia oxidation electrode prepared in Example 1 are calculated, as shown in FIG. Figure 8 The distance is limited to The Zn-Ni@SNC diatomic catalyst is more favorable for *N2H x+y The formation of Ni-Zn@SNC and the reaction energy barrier (ΔG*N2H x+y ) was significantly reduced, and the peak position (E p , the first maximum near the Fermi energy) and the d-band center (E d ) significantly upward.

[0074] In summary, the diatomic catalyst prepared by the present invention is simple to operate and environmentally friendly on the basis of effectively controlling the cost. The prepared diatomic electrocatalytic ammonia oxidation electrode is used in practical applications to produce NH4 + -N conversion rate is 100%, while 99.7% is converted into N2, and it can maintain high selectivity and catalytic activity for a long time, and the cathode synchronous hydrogen production rate is 0.34483mmol·mg -1 ·h -1 , excellent electrochemical performance, and has broad application prospects.

Claims

1. A method for preparing a diatomic catalyst for ammonia electrooxidation and simultaneous hydrogen production reaction, characterized in that: The steps include: (1) dissolving the metal salt M1 and the organic ligand in an organic solvent, stirring the reaction, washing the obtained material to remove impurities, and obtaining a pre-synthesized metal organic framework; (2) Firstly, the metal salt M2 and thioacetamide are dissolved in an organic solvent, stirred, and then the metal organic framework is added and stirred for a period of time, and then dried and ground to obtain a precursor; (3) The precursor obtained in step (2) is heated and pyrolyzed in an inert atmosphere, and then ground after cooling. The powdered solid obtained after grinding is acid-washed, and then washed and dried to obtain a diatomic catalyst.

2. The method for preparing a diatomic catalyst for ammonia electrooxidation and simultaneous hydrogen production reaction according to claim 1, characterized in that: In the obtained diatomic catalyst, the spacing between the diatomic active sites is 1.5~3.5Å.

3. The method for preparing a diatomic catalyst for synchronous hydrogen production by ammonia electrooxidation according to claim 1, characterized in that: The metal salt M1 is selected from one or more of zinc chloride, zinc sulfate, zinc nitrate, zinc gluconate, zinc acetate and hydrates thereof; The metal salt M2 is selected from one or more of chlorides, sulfates, nitrates and acetates of nickel, cobalt, chromium, copper, iron and manganese.

4. The method for preparing a diatomic catalyst for simultaneous hydrogen production by ammonia electrooxidation according to claim 1 or 3, characterized in that: The molar ratio of metal ions in the metal salt M1 to that in the metal salt M2 is 1-1.5:0.5-1.

5. The method for preparing a diatomic catalyst for simultaneous hydrogen production by ammonia electrooxidation according to claim 1 or 3, characterized in that: The mass ratio of the metal salt M1 and the organic ligand added in step (1) is 15-25:10-15; The molar ratio of metal ions to thioacetamide in the metal salt M2 added in step (2) is 3-4:8-12.

6. The method for preparing a diatomic catalyst for simultaneous hydrogen production by ammonia electrooxidation according to claim 1 or 3, characterized in that: The organic ligand in step (1) is dimethylimidazole.

7. The method for preparing a diatomic catalyst for simultaneous hydrogen production by ammonia electrooxidation according to claim 1, characterized in that: The organic solvent in step (1) and step (2) is selected from one of methanol, ethanol and butanol, and the stirring time is 12 to 24 hours.

8. The method for preparing a diatomic catalyst for simultaneous hydrogen production by ammonia electrooxidation according to claim 1 or 7, characterized in that: The heating temperature in step (3) is 800-1000°C, and the pyrolysis time is 1-3 h.

9. An application of a diatomic catalyst for simultaneous hydrogen production in ammonia electrooxidation prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The diatomic catalyst is loaded on a conductive substrate to prepare a diatomic ammonia electrocatalytic oxidation electrode; The diatomic ammonia electrocatalytic oxidation electrode is used in the ammonia electrooxidation and simultaneous hydrogen production reaction.

10. The use of a diatomic catalyst for simultaneous hydrogen production in ammonia electrooxidation according to claim 9, characterized in that: The loading amount of the diatomic catalyst on the conductive substrate is 0.5~3 mg / cm 2 .

Citation Information

Patent Citations

  • Preparation method of bimetallic site monatomic catalyst and application of bimetallic site monatomic catalyst in electrocatalytic ammoxidation total denitrification reaction

    CN116550355A